Risk-based pipeline integrity management: A road map for the resilient pipelines - Khan, Faisal; Yarveisy, Rioshar; Abbassi, Rouzbeh (Journal of Pipeline Science and Engineering, 2021)
Pipelines are the most vital energy-transportation mediums of today’s energy-intensive economies. To a level, pipeline integrity is tied to the continuous development and robustness of modern societies, where major failures may result in dire environmental, societal, and economic consequences. Therefore, pipeline safety and integrity are crucial for a sustainable future and responsible development. Pipeline integrity management has been a topic of interest for regulators, practitioners, and academicians alike. Over the past four decades, integrity management has evolved from prescriptive visual inspection and assessment to risk-based integrity management using real-time data. This paper aims to capture the evolution of risk-based methods in integrity management, focusing on the last two decades. The paper answers four primary questions:1What is integrity management, and how has it evolved?2How does the concept of risk fit in integrity management?3What are the methods used to assess and manage pipeline integrity?4How will integrity accommodate Industry 4.0?This article briefly defines the term integrity, how it has progressed and subsequently provides a structured review and analysis of the public domain literature. The paper focuses on risk-based methods adopted to different integrity management elements and applied at different stages of the pipeline’s life cycle. The paper concludes by evaluating the research progress, the gaps in knowledge, and their implication on adopting Industry 4.0.